2010
DOI: 10.1177/070674371005500503
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Suicide and Bullying in Childhood to Young Adulthood: A Review of Cross-Sectional and Longitudinal Research Findings

Abstract: S uicidal behaviours affect millions of teenagers each year, indicating a public health problem in need of attention and intervention. Suicide rates among young people have been increasing to such an extent that they are now the group at highest risk in one-third of countries, both in developed and in developing countries. 1,2 Bullying among school-age children is now recognized as a major public health problem in the Western world. In 2001, the Surgeon General of the United States published a report 3 emphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
190
1
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 364 publications
(227 citation statements)
references
References 65 publications
(131 reference statements)
18
190
1
18
Order By: Relevance
“…Furthermore, this research suggests that the greatest at risk group for adolescents engaged in bullying are those who are victims as well as perpetrators of bullying. Klomek et al (2010) reviewed cross-sectional and longitudinal findings related to bullying and suicidality. Their review confirmed the elevated level of risk associated with being a victim-perpetrator, as well as confirming the relationship between suicide risk and victimization.…”
Section: Bullying and Suicide During Adolescencementioning
confidence: 99%
“…Furthermore, this research suggests that the greatest at risk group for adolescents engaged in bullying are those who are victims as well as perpetrators of bullying. Klomek et al (2010) reviewed cross-sectional and longitudinal findings related to bullying and suicidality. Their review confirmed the elevated level of risk associated with being a victim-perpetrator, as well as confirming the relationship between suicide risk and victimization.…”
Section: Bullying and Suicide During Adolescencementioning
confidence: 99%
“…. 1319 bullying, os agressores (bullies) tendem a apresentar comportamentos antissociais, como o uso de drogas lícitas e ilícitas, além de serem potenciais pessoas em confl ito com a lei (Bender & Lösel, 2011;Farrington & Ttofi , 2011;Oliveira et al, 2016); as vítimas são propensas a estarem insatisfeitas com a vida, podendo apresentam tendências depressivas e suicidas (Costa, Xavier, Andrade, Proietti, & Caiaffa, 2015;Fleming & Jacobsen, 2009;Geel et al, 2014;Klomek, Sourander, & Gould, 2010;Roh et al, 2015); víti-mas/agressores tendem a apresentar baixos ín-dices de comportamento pró-social, frequentes difi culdades acadêmicas e predisposição para o desenvolvimento de transtornos psiquiátricos (Arseneault et al, 2006;Kim et al, 2005;Perren & Alsaker, 2006;Sourander et al, 2007). Os efeitos do bullying sobre as testemunhas variam de acordo com o envolvimento destes; por exemplo, pode ir da quase extinção de comportamentos relacionados com solidariedade e cooperação até sofrimento vivenciado por aqueles que se identifi cam com a vítima (Ribeiro, 2007).…”
Section: Introductionunclassified
“…L'intimidation subie serait en outre liée à plusieurs problèmes d'adaptation psychosociale à long terme pour les victimes, tel que démontré par des méta-analyses et des recensions des écrits récentes (p. ex. : García et Margallo, 2014;Gini et Pozzoli, 2013;Klomek et al, 2010;Ttofi et al, 2011, Ttofi et al, 2012van Dam et al, 2012). Comme le problème de l'intimidation subie est en progression dans les écoles primaires canadiennes (Beaumont et al, 2014;Savoie, 2007), la présente étude visait à mieux comprendre ses effets potentiels sur les difficultés d'adaptation psychosociale des élèves du primaire de milieux défavorisés pour éventuellement intervenir plus efficacement auprès des jeunes à risque.…”
Section: Discussionunclassified
“…Notamment, des méta-analyses et des recension des écrits récentes montrent un lien significatif entre l'intimidation subie à l'école primaire et plusieurs problèmes de santé mentale à l'adolescence et à l'âge adulte (García et Margallo, 2014;Gini et Pozzoli, 2013;Klomek, Sourander et Gould, 2010;Lepage, Marcotte et Fortin, 2006;Tobin et Duncan, 2007;Ttofi, Farrington, Lösel et Loeber, 2011;Ttofi, Farrington et Lösel, 2012;van Dam, van der Ven, Velhorst, Selten, Morgan et Haan, 2012). Compte tenu de sa forte prévalence et des impacts à plus ou moins long terme répertoriés chez les victimes, l'intimidation subie mérite une attention particulière à la fois de la part des chercheurs et des intervenants en milieu scolaire.…”
Section: L'intimidation Subie Est Un Phénomène Fréquent Dans Les éColunclassified
See 1 more Smart Citation